Middle ear packing materials: comparison between absorbable hemostatic gelatine sponge and sugarcane biopolymer sponge in rats - Bunzen,Débora Lopes (2014)
INTRODUCTION: Several biomaterials can be used in ear surgery to pack the middle ear or support the graft. The absorbable gelatin sponge is the most widely used, but it may produce fibrosis and impair ventilation of the middle ear. OBJECTIVE: This experimental study aimed to investigate the inflammatory effects of the sugarcane biopolymer sponge (BP) in the rat middle ear compared with absorbable gelatin sponge (AGS). MATERIALS AND METHODS: Prospective experimental study design. Thirty adult female Wistar rats were allocated to receive the BP sponge into the right ear and AGS into the left ear. Animals were randomly killed at 4 and 12 weeks post-procedure. Qualitative histological assessments were performed to evaluate the inflammatory reaction in the tympanic bullae. RESULTS: The BP sponge caused inflammation more intense and persistent than AGS. The BP was not absorbed during the experiment. Fibrosis was observed only in the ears with AGS. There were thickening of the mucosa and neoangiogenesis in the group of AGS. CONCLUSION: Despite inflammation, the BP sponge produced less fibrosis and neoangiogenesis compared to AGS. The sponge BP appeared to be a non-absorbable biomaterial in the middle ear.